2018
DOI: 10.1016/j.drugalcdep.2018.05.017
|View full text |Cite
|
Sign up to set email alerts
|

Prescription drug use, misuse and related substance use disorder symptoms vary by educational status and attainment in U.S. adolescents and young adults

Abstract: These results further suggest the importance of assessing educational status in adolescent and educational attainment in young adult PDM investigations. Adolescents poorly engaged in school or not in school appear especially in need of interventions to limit PDM and associated SUD symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
86
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 96 publications
(94 citation statements)
references
References 22 publications
7
86
1
Order By: Relevance
“…People with less than a four-year college degree had elevated HRs for opioid overdose mortality compared to those with graduate degrees. This is consistent with a previous studies of nonmedical opioid use including nationwide surveys of adolescents and young adults, [39,40] and studies in smaller areas [10]. This increase in risk of opioid misuse among people with low educational attainment may partially reflect downstream consequences such as less access to stable employment opportunities.…”
Section: Discussionsupporting
confidence: 92%
“…People with less than a four-year college degree had elevated HRs for opioid overdose mortality compared to those with graduate degrees. This is consistent with a previous studies of nonmedical opioid use including nationwide surveys of adolescents and young adults, [39,40] and studies in smaller areas [10]. This increase in risk of opioid misuse among people with low educational attainment may partially reflect downstream consequences such as less access to stable employment opportunities.…”
Section: Discussionsupporting
confidence: 92%
“…McCabe et al 19 found a greater number of educational-based differences in young adult sources, though neither that nor this study uncovered a strong and consistent pattern. Evidence suggests elevated PDM prevalence in adolescents not in school, 7,21 but it may be that while PDM engagement differs, the pattern of sources used by adolescents in different school enrollment/engagement situations is more invariant. Finally, the finding that males are more likely to use physician sources and that females are more likely to use multiple sources is consistent with work in both adolescents 15 and young adults.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence in young adults 19 and older adults 20 suggests that multiple sources for PDM are associated with higher rates of substancespecific (e.g., opioid SUD in those using multiple opioid sources) and any SUD, but this has not been evaluated in adolescents. Furthermore, evidence links adolescent school dropout with elevated PDM rates, 7,21 and educational status/attainment is associated with unique patterns of PDM sources in young adults. 19 Evaluating whether school enrollment/ engagement was associated with specific PDM sources could help direct school-and community-based interventions to limit PDM.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] There is a legitimate concern that the high prevalence of PDM places many adolescents and young adults at great risk for developing substance use disorder (SUD) symptoms and other adverse outcomes. [8][9][10] Based on the high addiction potential associated with PDM, adolescents and young adults may not mature out of PDM in the same way that they mature out of other experimental substance use. 11 Below, we briefly highlight the most commonly misused prescription medication classes: prescription opioids, stimulants, and sedatives/tranquilizers.…”
Section: Introductionmentioning
confidence: 99%